Effect of the Nutritional program according to (A) blood group on some physical variables for young footballers - Madab, Saad Abdul-zehra; Abid , Abass Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of the research is to design nutritional program according to (A) blood group and identify the effect of this program on the physical variables for young footballers ,and the researcher used the experimental approach to design two equivalent groups ( control and experimental) for the research sample of (10) for the season 2018-2019, and the researcher designed the nutritional program and prepared the physical tests .The researcher used the tools and devices appropriate for the research, and the researcher conducted an exploratory experiment to ensure the safety of the devices and tools ,and the researcher made special exercises for young footballers in advance for a period (8) weeks, at the rate of ( 3) units per week ,then or the researcher conducted a meta-tests and data processing and presentation and statistical and concluded that the effectiveness of the nutrition program according to (A) blood group as well as the researcher recommends the use of the nutritional program for players to develop football physical variables.